Critical Success Factors (CFSs) Implementation Cost-Benefit Analysis (CBA) Into Building Information Modelling (BIM) Application Through Malaysian Government Healthcare Projects - Omar, Fazleemardyana; Mohd Fateh, Mohd Ashraf; Gimhan Rathnagee Godawatte, Godawatte Arachchige (International Journal of Sustainable Construction Engineering and Technology, 2023)
The healthcare industry in Malaysia is proving to be one of the most competitive industries today. The sector is expected to grow to 127 billion ringgit (US$30 billion) by 2027, fuelled by increasing demand for healthcare services from an aging population, rising affluence, and increasing life expectancy. An advanced support system is required to ensure the deliverable and have a significant impact on national growth. One commonly used framework to support such crucial decisions in public projects and policies is Cost-Benefit Analysis (CBA). Integration of more support systems such as CBA and Building Information Modelling (BIM) will further enhance government construction project delivery. The objective of this research was to analyse critical success factors toward the integration of CBA and BIM implementation in Malaysian government healthcare facility projects. The outlined research objective aimed to enhance the integration of CBA within BIM implementation. A mixed-methods approach had been selected to collect the data and obtain the desired information. Via this mixed method, a questionnaire survey was conducted first, followed by the interview session. 90 numbers of respondents (populations) registered via the MYBIM Resources Network List (MyBIM CIDB), 74 numbers of respondents were set as a sampling set, and five (5) random respondents who participated in the early questionnaire survey were then selected to be further interviewed. The most CSFs quoted by the respondents are “peoples” via the interview and training and development via a questionnaire survey. This finding, comparatively, looks almost similar to what was found by previous research done in Hong Kong and in the Kingdom of Saudi Arabia's construction industry. Since CBA and BIM are the most important tools in construction and its deliverables, it is expected that the government, via their technical agencies, will properly and strictly enforce their current policies, which will be followed by all the players in the construction industry. In addition, more training should be provided to equip our construction industry professionals with the latest technology regarding CBA and BIM.